Brief report on a resilience workshop for professional rugby players - David John Edwards (Journal of Human Sport and Exercise, 2019)
This brief report constitutes an evidence based, evaluation of a resilience workshop for 328 male professional rugby players, with mean age of 25 and standard deviation (SD) of 4.7 years. Quantitative findings revealed significant changes in pre-test to post-test resilience scale scores. Qualitative findings indicated helpful experiential dimensions and those needing change. Integral findings pointed towards ongoing, humanistic, dynamic and systemic approaches involving all stakeholders in the professional rugby fraternity are recommended.